ANALISIS INTERCARRIER INTERFERENCE (ICI) SISTEM OFDM-MIMO STBC PADA KANAL FREQUENCY SELECTIVE FADING - I Wayan Diki Andriasmika; I.G.A.K. Diafari Djuni H; N.M.A.E. Dewi Wirastuti (Jurnal SPEKTRUM, 2019)
Wireless telecommunications requires high-speed access. One technique used tooWireless telecommunications requires high-speed access. One technique used toovercome multipath fading is Ortoghonal Frequency Division Multiplexing (OFDM). Theweakness of OFDM occurs on the mobile channel due to time variations in the channel, givingrise to intercarrier interference (ICI). The aim of the study is to determine the effect ofnormalized carrier frequency offset on ICI and the effect of frequency selective fading tapchannel. The simulation results show the system performance in calculating the Eb / N0 5 dBvalue that the greater the normalized carrier frequency offset (?), the worse the signal. Thesimulation results show the OFDM-MIMO system performance in calculating the Eb / N0 5 dBvalue that the greater the tap on the channel the worse the signal.vercome multipath fading is Ortoghonal Frequency Division Multiplexing (OFDM). Theweakness of OFDM occurs on the mobile channel due to time variations in the channel, givingrise to intercarrier interference (ICI). The aim of the study is to determine the effect ofnormalized carrier frequency offset on ICI and the effect of frequency selective fading tapchannel. The simulation results show the system performance in calculating the Eb / N0 5 dBvalue that the greater the normalized carrier frequency offset (?), the worse the signal. Thesimulation results show the OFDM-MIMO system performance in calculating the Eb / N0 5 dBvalue that the greater the tap on the channel the worse the signal.